Nitrones: A Potential New Alternative as Therapeutic Agents - Aliaga-Vidal, C; Aliaga-Vidal, C; Barriga-Gonzalez, G (BENTHAM SCIENCE PUBL LTD, 2017)
Background: Nowadays, nitrones are the most used spin traps to characterize free radicals in biological systems due to the versatility and variety depending on the types of radicals to study and that the half-lives of the species studied and/or detected increase considerably. In recent years, nitrones have been studied not only as free radical spin traps. Moreover, nitrones have been employed as therapeutic agents; in particular, those spin traps that are derived from alpha-phenyl-N-tert-butylnitrone (PBN). Nitrones as therapeutics agents have been used in the treatment of diseases related to oxidative stress such as neurodegeneration, cardiovascular disease and cancer. Conclusion: In this review, we focus mainly on those studies where nitrones have been used as potential therapeutic agents in diseases such as cancer, neurodegenerative, acoustic trauma and others. In addition, we have shown that they continue to be a potent and important tool as radical spin trap as well as their use as therapeutic agent.